Drug trafficking, international pressure, and domestic influence : Colombian-U.S. Relations, 1986-1994. (1998)
Throughout the 1980s the U.S. drug control strategy toward Latin America has relied on the use of external pressure -in the form of diplomatic, economic, and (sometimes) military sanctions- to force Latin American drug-producing and drug-exporting countries to cooperate fully with the U.S. in this anti-narcotics efforts.